Intervention in the Effort of Decreasing Anemia Incidence to Students of SMA N 4 Cikupa Kabupaten Tangerang - Firmansyah, Yohanes; Badruddin, Gabriella Hafidha; Christiani, Lidya (Disease Prevention and Public Health Journal, 2021)
Background: A survey conducted by the World Health Organization (WHO) in the span of time between 1993 and 2005 found that 1.62 billion people in the world had anemia, or around 24.8% of the world's population, with 30.2% (468 million) reproductive aged women. The research is a descriptive study as a means to perform early detection of anemia in adolescent girls with interventions in the form of counseling, improve adolescent knowledge, and improve adolescent attitudes and behavior at High School or Sekolah Menengah Atas Negeri (SMA N) 4 Cikupa. Method: This research is a descriptive quantitative analytic study where the sample was selected by simple random sampling. The population in this study were students of 4 Cikupa, Tangerang Regency of SMA N 4, Cikupa, Tangerang Regency. Results: The results of the study were (97.72%) respondents had increased their knowledge after counseling and (72.72%) respondents had improved their behavior and attitudes toward anemia. Participants (25%) were diagnosed with anemia and (75%) did not have anemia. Conclusion: improved knowledge is an important factor in reducing the prevalence of anemia in adolescent girls.